Peran krusial manajemen risiko strategis pada bank syariah - Prasetyo Utomo, Mahesa Dwi (Maliki Interdisciplinary Journal, 2024)
The role of banking as a dominant institution in the country and the importance of strict regulation and supervision to influence economic development. Risk management has a crucial role in banking, especially in Islamic banks in emerging markets. Effective risk management practices are necessary to identify problems early and take appropriate action. Implementing risk management can increase shareholder value, measure bank performance accurately, and create a strong infrastructure. Failure in strategic risk management can result in liquidity difficulties, bank closure, or bankruptcy. Risk determinants and mitigation efforts as well as the implementation of risk management in Islamic banks, including the responsibilities of the board of directors and supervisors. Product development, standardization of regulatory practices, human resource development, and marketing are also important factors in the development of Islamic banking.